PEMANFAATAN SENSOR PIEZOELEKTRIK SEBAGAI PENGHASIL SUMBER ENERGI LISTRIK ALTERNATIF MENGGUNAKAN TETESAN AIR HUJAN - Dhani Yonata Hariyono; Nazaruddin Nasution (Komunikasi Fisika Indonesia, 2023)
Indonesia is a tropical country whose renewable energy sources have not been optimally explored and developed. The advantages of a tropical climate are rain and heat, which should be put to good use to become a renewable energy source. One of the beneficiaries is the energy produced by rainwater using piezoelectricity. With the pressure of rainwater on the piezoelectric, the piezoelectric can produce electrical energy that can be stored for use. The amount of energy that can be generated directly depends on the piezoelectricity used and the rainfall. The method used in this research is to do experimental testing. The generated electrical energy is stored in a 12 V dry battery which has been rectified from AC (alternating current) to DC (direct current) using rectifier diodes. The results of the electrical input voltage are processed using the Arduino Uno microcontroller via a voltage sensor and stored using a data logger shield with an SD card and data. The results of this study show that the largest voltage and current are generated at 110.5 mm rainfall and a voltage of 35.50 V and a current of 209.95 mA is obtained. While the smallest voltage and current are generated at 9 mm rainfall and obtained a voltage of 2.89 V and a current of 17.1 mA.